Postpartum doula care and symptoms of depression and anxiety among BIPOC and Latina birthing parents: a longitudinal pilot intervention study - Jessica Hanlin; Laurel M. Hicks; Gabriela Alvarado; Alison Batwin; Michele Holland; Elizabeth Greenwell (Frontiers in Global Women's Health, 2026)
Background Perinatal mental health conditions are leading complications in pregnancy and postpartum in the United States, and Black, Indigenous, People of Color (BIPOC) and Latina birthing parents experience disproportionate postpartum mental health burdens and care inequities. Set within a high-income U.S. state, this study examines a population experiencing socioeconomic and structural barriers that may contribute to postpartum mental health vulnerability. Most participants were Medicaid beneficiaries facing barriers, including food insecurity, limited social support, and limited healthcare access. We explored the impact of postpartum doula care on symptoms of depression and anxiety in this cohort of BIPOC and Latina birthing parents as well as participant satisfaction, acceptability, and feasibility of the intervention. Methods In this single-arm longitudinal pilot ( N = 33), we investigated the effects of postpartum doula care on mental health markers among a cohort of birthing parents reporting elevated symptoms of depression or anxiety. This non-medical intervention consisted of in-home, postpartum doula care visits (∼24 h total, typically six visits of four hours each) within the first year postpartum. Data were collected at three timepoints (T1-baseline, T2-mid-study, T3-end point). Results Paired t-tests among participants completing all study assessments ( n = 24) demonstrated significant reductions in both depression and anxiety levels from T1 to T3. The intervention was successfully delivered, with participants completing the study receiving nearly the full intended dose of postpartum doula care. Participants reported high satisfaction, including perceived benefits to their postpartum experience, mood, and anxiety, and strong acceptability of postpartum doula care for future use. Conclusion Although larger, controlled studies are needed, these findings suggest that postpartum doula care is a promising strategy that warrants further evaluation for effectiveness, scalability and advancing perinatal mental health equity.